Development and application of a new base isolation system in low-rise buildings. (December 2021) - Behzad Talaeitaba, Sayed; Safaie, Mohamad; Zamani, Reza
Abstract: Application of base isolators undermines the drawback of earthquake to the structures. In recent decades, various base isolators have been applied, and several researchers have conducted research on the influence of base isolated structures. In this study, a rubber bearing with steel rings called RRB is designed and applied in 3 to 6- story steel and concrete structures, and the results are compared to fixed base and isolated base structures with lead rubber bearing (LRB). Isolators are first modeled in finite element software Abaqus, and hysteresis analysis is done, and effective stiffness and damping of each isolator is obtained. The average results for effective stiffness of the LRB is 110.88 (ton/m) and for the RRB is 82.48 (ton/m). The average damping for the LRB is 18.44%, and for the RRB is 47.02%. The analysis of structures is considered nonlinear time history and is done with the earthquake records of Kobe, Tabas and Manjil. The results of drift, acceleration and base shear are presented. The acceleration results of RRB isolated base structure show that 3, 4, 5 and 6-story buildings has a reduction by 42.16, 43.36, 51.83 and 57.16%. Moreover, the shear results of RRB isolated base structures comparing to the corresponding fixed base structure has had a reduction of 55.5, 47.16, 37.93 and 56.83 for 3, 4, 5 and 6-story structures. The results for drift indicate that utilization of the RRB leads to a decrease by 35.33, 50, 54.5% and 59.66 for 3, 4, 5 and 6-story structures, respectively.